Determinants of Co-operative Bank’s Profitability in Karnataka State: Evidence from Vijayapur District - R. Hiremath, Prof. Bharati (IJRDO - Journal of Business Management, 2018)
Financial performance of a bank indicates the strength and weakness of that particular bank by properly establishing the association between the items of the balance sheet and profit & loss account. The present study is a comparative analysis of the financial performance of Co-operative banks. The study considered a sample of 20 Co-operative banks for the period from 2008-09 to 2012-13. Profitability ratios were used in the study to measure the performance of the considered banks. The profitability ratios indicated that Interest Income, Interest Expended, Spread, NonInterest Income, Non Interest Expenditure, Burden, Net Profit & Return on Capital Employed proved the financial soundness of SSCB, BPCB, AUCB and MCB. But after monitoring the changes in these profitability ratios, it is clear that the banks have to improve its operational strategy; only then it will be able to attract more customers and investors. For sound financial health, banks need to put in more effort to be efficient in generating greater profits per rupee of sale. The results of the t-test disclosed that there is a significant difference in profitability performance of the Co-operative banks in Vijayapur District